The Portrayal of Palestinian and Israeli Suffering and Violent Incidents in Selected US Daily Newspapers - Falah, Ghazi-Walid (Journal of Holy Land and Palestine Studies, 2023)
This paper argues that editors of newspapers in the US, in their capacity to select and arrange news related to tragic events in Palestine/Israel, tend to follow an underlying political agenda largely conforming with US foreign policy towards Israel, the Palestinians and the Arab or Moslem world more generally. This is part of a popular American geopolitical imaginary, now being reconfigured through the primacy of ‘terror’ as the enemy number one of the American way of life, and most certainly, by proxy, of the Israeli way of life or the life of any Washington-oriented democracy. Reportage on cases of Palestinian tragedy and agony were represented as part of or the byproduct of protracted conflict within a kind of historical amnesia or bracketing out: Israeli state policy which victimises the Palestinians tends to be rendered invisible in such manipulation of reported reality. In other words, a deft editorial arrangement deflects possible blame on Israel by removing the events from their broader context and time frame. The reports centre on symptoms of the pathology rather than its underlying causes.